Stability analysis of road cut slopes in Sikkim Himalaya along national highway 10, India - Kuldeep Dutta; Nishchal Wanjari; Anil Kumar Misra (Geology, Ecology, and Landscapes)
The point-specific analysis of slope stability of road cut at nine locations was conducted along NH-10, between Rangpo and Ranipool in Sikkim, India. Kinematic analysis of discontinuities shows slope vulnerability to a union of failure types, namely, plane, wedge, and topple failure at different studied sites. Rock mass characterization was carried out on the basis volumetric joint count (Jv), RQD, RMR, and GSI. Appraisal of slope vulnerability to failure was done using traditional slope mass rating (SMR), Continuous SMR, Chinese SMR, and Q-slope stability method. Comparative analysis of different empirical methods proves a decent correspondence and shows that most of the cut slopes are under unstable to a partially stable condition. Stability method, Q-slope was used to analyse the stability conditions for 50%, 30%, 15%, and 1% probability of failure and to further find out stable slope angle for all the considered locations. The coalesced effort of the road cut stability analysis through kinematic and empirical methods will give insight into slope failure vulnerability along this highway by finding the most susceptible failure locations. The study will help to understand the dynamics of slope design for problematic stretches along NH −10 and adopt more effective remedial measures for better stability.